Contribution to research of thermal loads in commercial vehicles powertrain mounts - Demić, Miroslav D.; Glišović, Jasna D. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Due to the effects of excitations of road micro-roughness and the powertrain as well as due to the conditions of movement (acceleration, braking, curvilinear movement), the weights of commercial vehicles perform complex spatial oscillations. The negative impact of these movements or dynamic loads caused by them and transmitted to the supporting system of the vehicle can be reduced by a proper selection of the position and characteristics of the powertrain mounts. Elastic and damping forces in mounts perform mechanical work that turns into heat energy. Theoretical, experimental and combined methods can be used for the analysis of thermal loads of mounts. In this paper, research was carried out with theoretical methods using a mechanical model of the powertrain. Vibrations were observed on a freight vehicle powertrain of FAP 1314 middle-class vehicles. Bearing in mind the presence of classical (rubber-metal) and hydraulic mounts in modern commercial vehicles, the authors analysed the thermal loads of the mentioned vehicle type using a mathematical model.